Problem:
"x^2\\dfrac{\\partial^2 y}{\\partial x^2}+x(x-1)\\dfrac{\\partial y}{\\partial x}+(1-x)y=0" (1)
Let's image solution of the task in the next view:
"y=x^\\sigma(a_{0}+a_{1}x+a_{2}x^2+...a_{k}x^k+...)" (2)
Now subsitute equation (2) into equation (1):
"x^2\n(\\sigma\\times(\\sigma-1)\\times a_{0}x^{\\sigma-2} + \n(\\sigma+1)\\times\\sigma\\times a_{1}x^{sigma-1} +\n(\\sigma+2)\\times(\\sigma+1)\\times a_{2} x^{\\sigma}+ ...) +\nx(x-1)\n(\\sigma\\times a_{0}x^{\\sigma-1} +\n(\\sigma+1)\\times a_{1}x^{\\sigma} +\n(\\sigma+2)\\times a_{2}x^{\\sigma+1}+....) + \n(1-x)\n(a_{0}x^{\\sigma} + a_{1}x^{\\sigma+1} + a_{2}x^{\\sigma+2}+...)=0"
Or:
"(a_{0}x^{\\sigma}\\times\\sigma\\times(\\sigma-1) +a_{1}x^{\\sigma+1}\\times\\sigma\\times(\\sigma+1)+a_2x^{\\sigma+2}\\times(\\sigma+1)\\times(\\sigma+2)+...) +\n(a_0x^{\\sigma+1}\\times\\sigma+a_1x^{\\sigma+2}\\times(\\sigma+1)+a_2x^{\\sigma+3}\\times(\\sigma+2)+...) - \n(a_0x^\\sigma\\times\\sigma+a_1x^{\\sigma+1}\\times{\\sigma+1}+a_2x^{\\sigma+2}\\times(\\sigma+2)+...) +\n(a_0x^{\\sigma}+a_1x^{\\sigma+1}+a_2x^{\\sigma+2}+...)-(a_0x^{\\sigma+1}+a_1x^{\\sigma+2}+a_2x^{\\sigma+3}+...)=0"
Now equate all coefficient near "x^{\\sigma}, x^{\\sigma+1}, x^{\\sigma+2},..." to zero:
"\\begin{cases}\na_0\\times\\sigma\\times(\\sigma-1)-a_0\\times\\sigma+a_0=0\\\\\na_1\\times\\sigma\\times(\\sigma+1)+a_0\\times\\sigma-a_1\\times(\\sigma+1)+a_1-a_0=0\\\\\na_2\\times(\\sigma+1)\\times(\\sigma+2)+a_1\\times(\\sigma+1)-a_2\\times(\\sigma+2)+a_2-a_1=0\\\\\n...\n\\end{cases}"
From the first equation (we take that "a_0\\not=0" )we get: "(\\sigma-1)^2=0=>\\sigma=1"
Let's substitute this value to our system (3). Now we have:
"\\begin{cases}\na_0\\not=0 \\\\\na_1=0 \\\\\na_2=0\\\\\n...\n\\end{cases}"
So we have that all coefficient "a_k" (except "a_0" ) are equal zero. That means that:
"y=a_0x^\\sigma"
Also we know that "\\sigma=1". So solution of this problem is:
"y=a_0x",
where "a_0" is a different constant.
Comments
Leave a comment